The Role of The Village Government in The Implementation of Disaster Management Through the Disaster Resilient Village â€œSapto Manunggalâ€ in Kedungbendo Village - Tiani, Fitri Agus; Hilman, Yusuf Adam; Widiyanseno, Bambang; Ridho, Irvan Nur (Utan Kayu Publishing, 2022)
The objective of the study was to find out how the role of the village government in the implementation of disaster management through the Disaster Resilient Village â€œSapto Manunggalâ€ in the village of Kedungbendo. Disaster Resilient Village activities focus on the implementation of disaster management in a planned, integrated, coordinated, and comprehensive manner in order to provide protection to the community from threats, risks and impacts of disasters. The method in this study uses descriptive research with a qualitative approach. The findings in this study are that the implementation of disaster management is divided into 3 (three) stages, namely the pre-disaster stage, the emergency response stage and the post-disaster stage. The implementation of disaster management is defined as the establishment of a development policy that poses a risk of a disaster, disaster prevention activities, emergency response, and rehabilitation. In conclusion, the implementation of disaster management in Kedungbendo village has activities at every stage so the role of the village government in the implementation of disaster management includes prevention activities when disasters occur to recovery.Â Penelitian ini bertujuan untuk mengetahui bagaimana peran pemerintah desa dalam penyelenggaraan penanggulangan bencana melalui Desa Tangguh Bencana â€œSapto Manunggalâ€ di desa Kedungbendo. Kegiatan Desa Tangguh Bencana berfokus pada terselenggaranya pelaksanaan penanggulangan bencana secara terencana, terpadu, terkoordinasi, dan menyeluruh dalam rangka memberikan perlindungan kepada masyarakat dari ancaman, risiko dan dampak bencana. Metode dalam penelitian ini menggunakan penelitian deskriptif dengan pendekatan kualitatif. Hasil temuan pada penelitian ini bahwa penyelenggaraan penanggulangan bencana terbagi dalam 3 (tiga) tahapan yaitu tahap prabencana, tahap tanggap darurat dan tahap pasca bencana. Penyelenggaraan penanggulangan bencana didefinisikan sebagai penetapan sebuah kebijakan pembangunan yang berisiko timbulnya bencana, kegiatan pencegahan bencana, tanggap darurat, dan rehabilitasi. Kesimpulannya, penyelenggaraan penanggulangan bencana didesa Kedungbendo memiliki kegiatan di setiap tahapan sehingga peran pemerintah desa dalam penyelenggaraan penanggulangan bencana meliputi kegiatan pencegahan, saat bencana terjadi hingga pemulihan.